A Critical Discourse Analysis: Harvey Specter’s Power and Authority in the TV Series Suits Season 1 - Fakhrozi Muslim; Zia Hisni Mubarak (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study examines how power and authority are linguistically constructed in the television series Suits, focusing on the character of Harvey Specter in Season 1. The study aims to identify linguistic strategies used to establish professional authority within a legal workplace setting. The data consist of selected spoken dialogues depicting professional interactions between Harvey Specter and other characters in the law firm. Employing a qualitative approach, the research applies Fairclough’s Critical Discourse Analysis framework, supported by theories of workplace discourse by Holmes and Stubbe and Weber’s concept of legal-rational authority. Data were collected through observation and transcription of relevant scenes and analyzed by identifying utterances that reflect power relations. The findings reveal that Harvey’s authority is constructed through strong modality, material processes, and direct commands that position him as the primary decision-maker. You're not a lawyer until I say you are" demonstrates the use of high modalities that place Harvey as a determinant of professional identity, while imperatives such as "Now get to work" function as direct commands with no negotiation space, which linguistically reinforces asymmetrical power relations. Additionally, his control over conversational flow and task distribution reinforces hierarchical relations, while expectations of autonomy reflect merit-based professional values. The study concludes that spoken discourse in television series can effectively represent institutional power dynamics similar to those found in real professional environments.